STRATEGI PENGEMBANGAN DAYA TARIK WISATA TUKAD BINDU BERBASIS MASYARAKAT DI KELURAHAN KESIMAN KOTA DENPASAR - Christina Risma Lovieta; Putu Eka Wirawan; I Gusti Ayu Melistyari Dewi; I Gusti Ayu Eka Suwintari (Journal of Tourism and Interdiciplinary Studies, 2023)
The tourist attraction of Tukad Bindu was originally a river that was used as garbage dump by local community, which seemed haunted and dirty. However, because of the concern and participation of the local community, the Bindu River was managed and developed by the Tukad Bindu Foundation to become a tourist attraction. Even though has become a tourist attraction, although there are still many shortcomings with respect to management and development, consequently, this study's goal is to create alternate development strategies that are more effective, so it will able to maintain its existence and become a sustainable tourist attraction as an example for other tourist attraction, to continue to pay attention to environmental sustainability and provide an impact on increasing the community's economy. This study used a method of qualitative description, which was obtained through data collection techniques of observation, interviews, questionnaires and document studies. As well as data analysis techniques, namely analysis techniques using the IFAS-EFAS matrix, IE matrix, SWOT matrix, and QSPM matrix. The results of this research are that Tukad Bindu Tourism Attraction is in quadrant I, namely supporting an aggressive strategy by taking advantage of opportunities and strengths owned by Tukad Bindu Tourism Attraction as much as possible in developing tourism products. Furthermore, based on the QSPM analysis, there are two priority strategies that get the highest STAS, namely the WO1 Strategy 6.21 conducting regular promotions and the SO1 strategy 6.16 creating new tourism activities.